Morphological alterations in the epithelium of the oral mucosa of rats (Rattus norvegicus) submitted to long-term systemic nicotine treatment - Caldeira, Eduardo Jose; Fabrega Carvalho, Cesar Alexandre; Padovani, Carlos Roberto; Camilli, Jose Angelo; Garcia, Progresso Jose; Alves Cagnon, Valeria Helena (Elsevier B.V., 2007)
Smoking is considered to be the most albeit preventable cause of diseases and premature deaths in the history of mankind. The local action of tobacco on the oral mucosa can cause precancerous and cancerous lesions. However, there is not enough evidence to establish all the systemic effects caused by nicotine on the organism. Thus, the aim of the present study was to characterize the cellular changes of the cheek mucosa of rats submitted to long-term systemic nicotine treatment. Twenty male rats were divided into two experimental groups: a nicotine group and a control group, each consisting of 10 animals. The nicotine group was injected daily with 0.250 mg of nicotine per 100 g of body weight. All animals received a solid diet and water ad libitum. After 90 days of treatment, all animals were weighed and sacrificed. Samples of cheek mucosa were collected for light and transmission electron microscopy. The results revealed oral epithelium containing atypical cells that were characterized by atrophy, cell membrane disorganization and tissue damage. It was concluded that systemic administration of nicotine damaged the cellular integrity of the oral mucosa, impairing tissue function and predisposing the tissue to the action of different pathogenic agents and also to that of other carcinogenic substances present in tobacco. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: oral mucosa; structure; nicotine treatment